Investigation of solar food dryer characteristics / Sharizan Shaifulyazan and Nor Fazira Reduan - Shaifulyazan, Sharizan; Reduan, Nor Fazira (2005)
This study is about an investigation of solar food dryer characteristics. The main objective of this experiment is to study the effectiveness of drying method, temperature characteristics, and an airflow pattern. This project is a follow up from the project before this. Some modification and improvement have been done to the previous project. To ensure the solar food dryer that has been modified is well functioning, several experiments need to be done. For further clarification, this report will cover all the result from the experiments that we had done. It is hope that this study will help further understanding and the development of the solar energy.